Investigation of Employability Perceptions of Sports Science Students - Nuh Osman Yıldız,; Zülbiye Kaçay,; Güçlü Özen, (Journal of Educational Issues, 2024)
This study, which was conducted to examine the employability perceptions of students studying in the field of sports sciences in terms of gender, department, type of university, work in the field of diploma and level of foreign language knowledge, was designed according to correlational survey and causal comparison methods. In determining the sample of the study, accessible sampling method, which is one of the non-random sampling methods, was used. The sample in question consists of a total of 206 participants, 99 females (48.1%) and 107 males (51.9%). As a measurement tool the “Employability Perception Scale” (IEAS) developed by Rothwell et al. (2008) and adapted into Turkish by Karlı (2016), was used in the study. According to the results of the analysis, a significant difference was determined in terms of gender variable in the University Prestige sub-dimension (p < 0.05). No significant difference was determined in terms of other sub-dimensions and variables. As a result, it is possible to state that the employability perception of the students studying in the field of sports sciences is high, that the female participants perceive their university as more prestigious than the male participants, and this contributes positively to their belief that they can be employed in this situation.